Protective Effect of Thyme Extract on Albino Rats Exposed to Paraquat - Mahmood, Nazar M. Shareef (Kurdistan Journal of Applied Research, 2022)
Paraquat (PQ), as a frequently used compound in many applications while the herbal providing is vigorously used in the curing of broad spectrum diseases such as liver disease, the influence of thyme extract or Thymus vulgaris L. (T.vulgaris) and their constituents was previously reported. The main target goal of the present study, is to explore the influence of T.vulgaris extract toward PQ induced toxicity in male albino rats. The current study was conducted on thirty-two (32) male albino rats, they were separated equally and randomly upon four (4) groups, all groups fed normal diet and drunk tap water ad libitum as following; the first group was considered as control. The second group was treated with PQ (0.3ml/rats) orally by needle gavage, the third group as administered with PQ (0.3ml/rats), and 200ml/kg body weight (BW) of T.vulgaris extract orally by needle gavage, the fourth group was administered with 200ml/kg BW of T.vulgaris extract orally by needle gavage. The treatment duration was continued for eight executive days. Paraquat administration showed significant decrease in BW, food intake, liver, kidney weight also PQ increased malondialdehyde (MDA), low density lipoprotein (LDL), alkaline phosphatase (ALP) and, uric acid (UA) significantly. Therefore, the current results indicate that, the herbicide PQ showed adverse effects through initiation of lipid peroxidation, while T.vulgaris extract produced a significant recovery in ameliorating some aspects of PQ toxicity.